(untitled) (EAAE Annual Conference Proceedings, 2023)
Some territories encounter an accumulation of difficulties, despoiling of resources, slavery, maltreatment, then abandonment with pollution, poverty, illiteracy, unemployment, diseases... The mining basin of the Nord and Pas-de-Calais is a good illustration. It was exploited from the beginning of the 18th century for its coal. Despite its recognition in 2012 as a Unesco World Heritage Site, it remains a territory in economic decline and whose social indicators are alarming.